2022
DOI: 10.3390/ani12030369
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death and Pathological Findings in Stranded Harbour Porpoises (Phocoena phocoena) from Swedish Waters

Abstract: Harbour porpoises (Phocoena phocoena) are useful indicators of the health of their wild populations and marine ecosystems, yet their elusive nature makes studying them in their natural environment challenging. Stranded porpoises provide an excellent source of data to study the health and biology of these animals and identify causes of death, diseases and other threats. The aim of this study was to document pathology, and where possible, cause of death in porpoises from Swedish waters. Post-mortem examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Recent necropsy data on stranded animals examined from Swedish waters show that bycatch, when considered together with probable bycatch, is the most frequent cause of death, supporting previous studies [1]. The carcasses of stranded animals are often in poor states of preservation due to decomposition, handling, scavenging, the delay between stranded animals being reported and collected for necropsy, and the possibility of carcasses drifting for extended periods before stranding.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Recent necropsy data on stranded animals examined from Swedish waters show that bycatch, when considered together with probable bycatch, is the most frequent cause of death, supporting previous studies [1]. The carcasses of stranded animals are often in poor states of preservation due to decomposition, handling, scavenging, the delay between stranded animals being reported and collected for necropsy, and the possibility of carcasses drifting for extended periods before stranding.…”
Section: Introductionsupporting
confidence: 67%
“…Harbour porpoises (Phocoena phocoena) are top predators in temperate marine ecosystems and the only permanent cetacean residents in Swedish waters [1]. Globally and in Europe, the harbour porpoise is listed by the International Union for Conservation of Nature (IUCN) as being of Least Concern (LC) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the southernmost parts of the North Sea, specifically Belgium and Northern France, bycatch proportions were similar to those we reported for the Netherlands (15%, Jauniaux et al, 2002), although mass bycatch mortality events have also been reported from Belgium (Haelters and Camphuysen, 2009) before recreational set-netting was banned there. In Sweden, 31% of all post-mortem examined porpoises between 2006 and 2020 most likely died following bycatch (Neimanis et al, 2022). Bycatch numbers probably run into the thousands of animals per year in the Danish North Sea (Vinther and Larsen, 2004).…”
Section: Accidental Bycatch In Fisheriesmentioning
confidence: 99%